2017
DOI: 10.3390/ijms18030676
|View full text |Cite
|
Sign up to set email alerts
|

ATRAP Expression in Brown Adipose Tissue Does Not Influence the Development of Diet-Induced Metabolic Disorders in Mice

Abstract: Activation of tissue renin–angiotensin system (RAS), mainly mediated by an angiotensin II (Ang II) type 1 receptor (AT1R), plays an important role in the development of obesity-related metabolic disorders. We have shown that AT1R-associated protein (ATRAP), a specific binding protein of AT1R, functions as an endogenous inhibitor to prevent excessive activation of tissue RAS. In the present study, we newly generated ATRAP/Agtrap-floxed (ATRAPfl/fl) mice and adipose tissue-specific ATRAP downregulated (ATRAPadip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Furthermore, PVAT contains different phenotypes of adipocytes i.e., white, brown, and beige adipocytes; and phenotype variability or changes in adipocytes in PVAT have been suggested to lead to different pathological roles in vascular disorders [1]. To this point, interestingly, researchers reported that decreased PVAT ‘browning’ in thoracic aortas of aging spontaneously hypertensive rats (8 wks vs. 16 wks) was associated with attenuated vasodilation effects of PVAT [43], but ATRAP in brown adipose tissue does not affect the development of obesity-related metabolic disorders [44]. Future studies investigating the relationship between changes in adipocytes phenotype and PVAT effects would provide significant mechanistic insight in the SHRSP.ZF model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PVAT contains different phenotypes of adipocytes i.e., white, brown, and beige adipocytes; and phenotype variability or changes in adipocytes in PVAT have been suggested to lead to different pathological roles in vascular disorders [1]. To this point, interestingly, researchers reported that decreased PVAT ‘browning’ in thoracic aortas of aging spontaneously hypertensive rats (8 wks vs. 16 wks) was associated with attenuated vasodilation effects of PVAT [43], but ATRAP in brown adipose tissue does not affect the development of obesity-related metabolic disorders [44]. Future studies investigating the relationship between changes in adipocytes phenotype and PVAT effects would provide significant mechanistic insight in the SHRSP.ZF model.…”
Section: Discussionmentioning
confidence: 99%
“…DRAXIN was related to Akt, which could impact milk synthesis [55,56]. AGTRAP was reported to have a functional role in adipose metabolism [57].…”
Section: Discussionmentioning
confidence: 99%
“…The GTT and ITT were performed as previously described 15 , 47 . Briefly, for the GTT, blood glucose concentrations were measured with a blood glucose test metre (Glutest Neo Super; Sanwa-Kagaku) using blood samples that were taken from the tail tip of overnight-fasted mice.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNAs were extracted from WAT, interscapular BAT, and soleus muscle tissue with ISOGEN (Nippon Gene), and the cDNA was synthesized using the SuperScript III First-Strand System (Invitrogen). Real-time quantitative RT-PCR was performed with an ABI PRISM 7000 Sequence Detection System by incubating the reverse transcription product with TaqMan PCR Master Mix and a designed Taqman probe (Applied Biosystems), essentially as described previously 47 . The mRNA levels were normalized to those of the 18SrRNA or glyceraldehyde-3-phosphate dehydrogenase (GAPDH) control.…”
Section: Methodsmentioning
confidence: 99%